Pelatihan Dasar Las Listrik untuk Masyrakat Sekitar Politeknik Penerbangan Palembang - Setiyo, Setiyo; Soleh, Asep Muhamad; Handayani, Ni Putu Heni; Trema, Frendy Khan (Jurnal Pengabdian Kepada Masyarakat, 2024)
Welding can be interpreted as joining two pieces of metal to the point of metal recrystallization, with or without additional materials, and using heat energy as a solvent for the material to be welded. This community service activity is in the form of basic electric welding training activities that aim to provide knowledge and skills for the community in the field of welding using electric welding equipment. The benefits of providing this knowledge of skills are that participants can use electric welding equipment correctly, apply safety procedures when welding, and create new jobs. Community service activities were conducted at Kalimarau Berau Airport with participants from airport employees and the surrounding community. The method used was training, carried out by providing welding theory and practice. Participants were provided with occupational safety and health materials as a procedure for welding practice using electric welding equipment. The implementation of community service activities succeeded in increasing the knowledge of participants, with an average value of good as measured by the welding practice results. Hopefully, this activity can improve the skills of the community around the airport in the field of electric welding.